Formation of social competence of future officers as an element of effective interaction of the security and defense sector with civil society - Mirshuk , O. (Problems of Engineer-Pedagogical Education, 2023)
The article considers the necessity of forming the social competence of future officers. The current state of Ukrainian society and the need to introduce new forms of work with subordinates are analyzed. The role of civil society in the process of democratization of the security and defense sector is analyzed. The study of interaction between civil society and the security and defense sector is analyzed. It is concluded that insufficient attention is paid to the issue of the development of social competence of future officers; the developed social competence is the foundation for successful interaction of the security and defense sector with the civilian sector. The mechanism of the development of social competence is analyzed. Social competence is analyzed in the context of social work with subordinates. It is concluded that in the conditions of hostilities, social work with servicemen and their families becomes one of the priority tasks in the work with personnel. The concept of social work includes restoration of physical and mental strength of military personnel, correction of their personal attitudes, communication with representatives of various social groups, assistance in adaptation to specific features of military service. The role of social competence of future officers in interaction with civil society is analyzed.